Structural Requirements for Activity of Phenoxazines fro Reversal of Drug Resistance in the Cancer Cells - Eregowda, G.B.; Krishnegowda, G.; Kalpana, H.N.; Channu, B.C.; Dass, C.; Horton, J.K.; Houghton, P.J.; Thimmaia, K.N. (Asian Journal of Chemistry, 2010)
In the course of a chemical program aimed at identifying chemically useful modulators of MDR in cancer therapy, a series of twentyone 2-trifluoromethyl- N10-substituted phenoxazines (1-21) has been synthesised. The novel 2-trifluoromethylphenoxazine (1) was prepared by the pyrolytic condensation of 2-bromophenol and 4-chloro-3-nitrobenzotrifluoride as outlined in Scheme-I. This compound undergoes N-alkylation in the presence of phase transfer catalyst (PTC). Stirring of 2-trifluoromethylphenoxazine with 1-bromo-3-chloropropane or 1-bromo-4-chlorobutane in a two phase system consisting of an organic solvent (benzene) and 6N potassium hydroxide in the presence of tetrabutylammonium bromide leads to the formation of compounds 2 and 9 in good yield. N-(ω-chloroalkyl)and N-(chloroacetyl) analogues were found to undergo iodide catalysed nucleophilic substitution reaction with various secondary amines including N,N-diethylamine, N,N-diethanol-amine, morpholine, piperidine, pyrrolidine and (β-hydroxyethyl)-piperazine. Purified products were characterized by UV, IR, 1H and 13C-NMR and mass-spectral data. The lipophilicity expressed in log10 P and pKa of compounds were determined. The effect of 1-21 at 100 μM on the steady-state accumulation of vinblastine (VLB) was studied in KBChR-8-5 cells and the data revealed that the compounds (3-8, 10, 12-15) exhibited a significant VLB uptake enhancing effect (8.3-58.5-fold relative to control) compared to a standard modulator, verapamil (VRP) (7.5-fold). These eleven compounds caused a 1.10-7.82- fold greater uptake of VLB than did a similar concentration of VRP. Comparison of the derivatives for their ability to potentiate the uptake of VLB revealed that they largely follow the order: N10-propyl > N10-butyl > N10-acetyl compounds. To determine whether the increase in VLB uptake upon coincubation with 1-21 modulators was due to a slowing of P-gp mediated efflux, KBChR-8-5 cells were loaded with [3H] VLB in the absence of modulator and efflux examined in the absence or presence of 100 μM of 8 or VRP. Less than 10% in the absence or about 40% of cell associated VLB in the presence of 100 μM 8 remained at the end of a 2 h efflux period, suggesting that modulator 8, like VRP, is able to inhibit p-glycoprotein (P-gp) mediated efflux. Cytotoxicity was determined and the IC10 and IC50 values lie respectively in the range 0.1-30.9 μM and 2.1-70.9 μM for KBChR-8-5 cells. Substitution of hydrogen by CF3 in C-2 of phenoxazine ring caused a greater enhancement in the antiproliferative protency by 1.1-3.3-fold for KBCHR-8-5 cells than their counterparts, presumably due to increased hydrophobicity. Compounds at IC10 were evaluated for their efficacy to modulate the cytotoxicity of VLB in KBChR- 8-5 cells and compounds 3, 5, 11 and 13, like VRP, were able to completely reverse the 24-fold resistance of KBChR-8-5 cells to VLB. The structural features for reversal of MDR seem to include a hydrophobic phenoxazine ring with a —CF3 in C-2 position and a tertiary amino group at a distance of three or four carbon chain from the tricyclic ring. Examination of the relationship between partition coefficient and cytotoxicity or anti-MDR activity showed no correlation suggesting that lipophilicity is not the sole determinant of potency for biological activity.